IMPLEMENTASI MODERASI AGAMA DI LEMBAGA PENDIDIKAN - Dewiwahyuto sejati (STAI Sufyan Tsauri Majenang, 2023)
Indonesia is a country full of diversity, and multi-religion, and culture. So it is necessary to have a religious moderation education in education. Religious moderation in educational institutions is very necessary so that they are educated to appreciate diversity from an early age and not commit a conflict caused by religion. This article aims to write about the challenges of creating an environment and the benefits of religious moderation in institutions, as well as strategies in implementing religious moderation. This research uses the literature review method by collecting various data through books or related articles then analyzed and described. The challenges in creating a multireligious learning environment include differences in religious views and understanding. The second challenge is the difficulty of building understanding and respect for religious differences to students. The benefits of religious moderation in institutions include inclusive learning, the second is strengthening tolerance and religious differences, and the last is, increasing understanding and knowledge of religion holistically. Strategies and approaches in implementing religious moderation in educational institutions can be done through the development of government and ministry of religion policies, which can be implemented by institutions with the help of various parties, namely, the school institution, teachers and religious communities in the institution. Keywords: Religious Moderation, Islamic Education, Multicultural Education